PARADIGMA KONSEP ILMU DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Farandika Nanda Pratama; Nur Ahmad; Siti Latifatun Nisak (UIN ANTASARI BANJARMASIN, 2024)
This study discusses the concept of knowledge in Islamic educational philosophy by highlighting the acquisition of knowledge, classification, and the role of integration and Islamization of knowledge in the Islamic education system. Using a literature study and thematic analysis approach, this study reveals that Islamic educational philosophy is not only based on rationality and empirical experience, but also emphasizes the role of the heart as a source of knowledge. The main findings of this study contribute to offering the importance of implementing a revelation-based and rationality-based knowledge integration model in the Islamic education curriculum to address global challenges. One implementation of this concept is seen in the education model at SMP Pondok Modern Selamat Kendal and MAN Insan Cendekia Pekalongan, which have successfully implemented the integration of religious knowledge and general knowledge in their curriculum. Therefore, it is recommended to restructure the learning system that aligns religious knowledge and general knowledge in order to create an Islamic education that is adaptive to the development of the times.